The Effects of Two Different Protocol of General Anesthesia on Clinical Body Health Status in Pigeons (A comparative Study) (Indian Journal of Animal Production and Management, 2026)
Twelve pigeons were used to compare anesthetic efficacy and clinical effects of medetomidine combined with ketamine (MK) to those of diazepam combined with ketamine (DK). The drugs were given intramuscularly and the anesthetic and physiological parameters were recorded along the experiment. The anesthetic parameters represent by onset of analgesia which appear in DK faster than MK group, time of anesthesia (Surgical time) and recovery time were showed longer time in MK group than DK group. The physiological parameters were represented by pulse rate, which showed increase at 10 minutes in MK group. However, at the end of experiment,it showed increase in DK group. SpO2 parameter showed an increase at the first 20 minute in all groups, but then, it showed decrease at 30 minute in DK group. The cloacal temperature showed gradually decrease during the experiment period. This study showed that medetomidine and ketamine together may be suggested for a number of regular pigeon surgical procedures because it provides a longer operative duration than a combination of diazepam and ketamine. According to the study's results, In order to increase animal production by decreasing anesthetic morbidity and mortality, providing a careful and stress-free anesthetic regimen, it is highly recommended to use medications with low adverse responses and side effects.
Keywords: Anasthesia, Diazepam, Ketamine, Medetomidine, Pigeons.